2013
DOI: 10.1371/journal.pone.0056104
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Phenolic Compounds Extracted from Propolis and Their Activity in the Yeast Saccharomyces cerevisiae

Abstract: We have here investigated the activities of Slovenian propolis extracts in the yeast Saccharomyces cerevisiae, and identified the phenolic compounds that appear to contribute to these activities. We correlated changes in intracellular oxidation and cellular metabolic energy in these yeasts with the individual fractions of the propolis extracts obtained following solid-phase extraction. The most effective fraction was further investigated according to its phenolic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Therefore, the authors concluded that the phenolic profile of Slovenian propolis is comparable to that of European propolis. [51,52] More recently, a group of research has reported that propolis samples from Slovenia, Croatia and France, mainly reflected patterns characteristic of blue-type propolis rich in flavonoids and with low quantity of phenolic acids. [53] Ethanolic extracts of propolis from several locations in Croatia, analyzed by several methods such as GC/ MS, two-dimensional thin-layer chromatography, HPLC-thin-layer chromatography among others, had relatively high amounts of flavonoids besides the presence of phenolic acids.…”
Section: Southern European Coastmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the authors concluded that the phenolic profile of Slovenian propolis is comparable to that of European propolis. [51,52] More recently, a group of research has reported that propolis samples from Slovenia, Croatia and France, mainly reflected patterns characteristic of blue-type propolis rich in flavonoids and with low quantity of phenolic acids. [53] Ethanolic extracts of propolis from several locations in Croatia, analyzed by several methods such as GC/ MS, two-dimensional thin-layer chromatography, HPLC-thin-layer chromatography among others, had relatively high amounts of flavonoids besides the presence of phenolic acids.…”
Section: Southern European Coastmentioning
confidence: 99%
“…In other countries of Southern European Coast, such as Turkey, chemical composition of propolis has widely investigated by several authors. Quercetin (26), rutin (48), chrysin (2), pinocembrin (3), pinostrobin chalcone (49) and pinobanksin (1) and its derivatives were the most repeated flavonoids found in various simples of propolis from Turkey using different method of analysis such as gas chromatography-mass spectrometry (GC/MS), high-performance liquid chromatography (HPLC) and ultrahigh-performance liquid chromatography with a linear ion trap-high resolution Orbitrap mass spectrometry system (UHPLC-LTQ/orbitrap/MS/MS), [73,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] while Erdogan et al [96] have reported the presence of other flavonoids such as gallocatechin (50), epigallocatechin (51) and myricetin (52) in Anatolian propolis submitted to a pressurized liquid extraction. Other authors did not report the presence of flavonoids in Turkish propolis originating from Hatay, Ankara-Kazan and Mugla-Marmaris, [97 -100] at the same time they declared that terpenes such as αand β-eudesmol, isopimaric acid (42), dehydroabietic acid (53) and abietic acid (54) ( Figure 4) were included in the bioactive compounds of tested propolis samples.…”
Section: Southern European Coastmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, the reagent thiobarbituric acid generates adduct with malondialdehyde, which is detectable spectrophotometrically at 532 nm. Besides the aforementioned method, cell viability assays are also employed in assessing oxidative damage in yeast, which evaluates the stress tolerance increase caused by treatment with antioxidant compounds [71]; mitochondrial function assays, since many apoptotic processes start in this organelle [72]; measurement of intracellular reactive oxygen species formation, using 2,7-dichloroluorescein as indicator [71,73]; protein carbonylation tests [74,75], which is also formed as consequence of oxidative damage; assessment of energetic metabolism and enzymatic activity associated with the stress response [67,74], among other methods.…”
Section: Antioxidant Activity Assaysmentioning
confidence: 99%
“…Regarding antioxidant activity at a cellular level, compounds showing antioxidant activity in vitro or in foods do not necessarily possess the same activity in the cells (21). If not injected, there will always be a GI digestion step, where peptides will be modifi ed, e.g.…”
Section: Antioxidant Activity In the Cells And Cellular Metabolic Energymentioning
confidence: 99%